Continuidade de painéis de laje alveolar em edifícios - Camillo, Carolina Alvares (Universidade Federal de São Carlos, 2012)
The floors consist of hollow core slabs are being increasingly used in Brazil, because it can overcome large spans, have a low self-weight, allow fast assembly, require no shoring in many situations and are more economical than other solutions. These floors are normally designed for ease of implementation, so that the slabs act as simply supported, without continuity. This work presents a roadmap of calculation and verification based on known theoretical models and tests already carried out considering that the hollow core slabs of pavement work as continuous. This continuity is made by adding passive reinforcement in the topping region. The calculation procedures are also detailed for the situations in which there are alternate accidental actions, as well as the situation in which there are concentrated mobile loads acting on the floor. Numerical examples comparative considering continuity with the situation simply supported show what can be achieved: the active reinforcement economy, increasing the value of accidental load and checks excessive deformation that is not checked on a system simply supported. Some situations are also pointed in which the consideration of continuity fails to bring great advantage. In all the examples developed are shown the details required to perform continuity. Every calculation methodology is based on Brazilian codes and should be noted that the calculations are done considering the simultaneous loss of prestressing. At the end of the work are proposed studies that may be performed to improve understanding of the behavior of pavements with continuous hollow core slabs.
Continuity of hollow core panels on buildings
Keywords: Concreto pré-moldado; Pré-fabricados; Lajes alveolares; Lajes de Piso; Continuidade; Pavimentos de edificações; Concrete; Precast; Hollow core slab; Floors; Continuity; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL